Physicochemical, structure properties and in vitro hypoglycemic activity of soluble dietary fiber from adlay (Coix lachryma-jobi L. var. ma-yuen Stapf) bran treated by steam explosion - Tang, Xinjing; Wang, Zhirong; Zheng, Jiong; Kan, Jianquan; Chen, Guangjing; Du, Muying (Frontiers in Nutrition, 2023)
To enhance the content of adlay bran soluble dietary fiber (SDF) and improve its functionality, we investigated the influences of steam explosion (SE) on the physicochemical, structural properties and in vitro hypoglycemic activities of adlay bran SDF. The cellulose, hemicellulose and lignin contents of adlay bran decreased significantly after SE treatment. When the SE strength was 0.8 MPa for 3 min, the SDF content was 9.37%, which was a significant increase of 27.48% compared to the control. Under these conditions, SDF showed the highest oil-holding capacity (2.18 g/g), cholesterol adsorption capacity (27.29 mg/g), glucose adsorption capacity (15.54 mg/g), glucose dialysis retardation index (36.57%)and α-Amylase activity inhibition ratio (74.14%). Compared with SDF from untreated adlay bran, SDF from SE-treated adlay bran showed lower weight molecular. In addition, differential scanning calorimetry (DSC) measurement showed that the peak temperature of SDF from adlay bran treated by SE increased by 4.19 ℃ compared to the untreated SDF sample. The structure of SDF from adlay bran treated by SE showed that the SDF surface was rough and poriferous and the specific surface areas increased. In conclusion, SE pretreatment increases the content of SDF in adlay bran and improves its physicochemical, structural properties and biological activities, which will be beneficial for the further exploitation of adlay bran.